A Copper Complex as Catalyst in Proton Reduction. Issue 28 (10th July 2017) - Nestke, Sebastian; Kügler, Merle; Scholz, Julius; Wilken, Mona; Jooss, Christian; Siewert, Inke
Abstract: Invited for the cover of this issue is the group of Inke Siewert from Universität Göttingen, Germany. The cover image shows a copper complex that catalyzes the electrochemically driven hydrogen evolution reaction (HER) in buffered purified water and seawater. Abstract : As we observed catalytic activity at pH 8, we thought it was worth testing the catalytic activity in seawater… Read more about the story behind the cover in the Cover Profile and about the research itself on page 3376 ff (https://doi.org/10.1002/ejic.201700154 ).